Analysis of Spring Damage in the Chamber Actuator - Nasution, Raven Rullyapatra; Rudi Saputra (Greenation Research & Yayasan Global Resarch National, 2024)
Spring, which has the function to help the valve operate so that it can be fully closed and fully open, has a very vital role in the continuous operation of the chemical industry. When a problem occurs, muddy fluid is found in the spring actuator chamber which causes the valve not to operate and not be in full close condition. The purpose of this study is to find the causes of the Spring Actuator failure in the chemical industry. This research was specifically directed at a broken Spring Actuator to determine the cause of the failure/damage. The tests carried out were: fractography, metallography (microstructure), chemical composition analysis, hardness test, and scanning electron microscope (SEM) energy dispersive x-ray (EDX) analysis. The results of the macrographic examination showed that the spring fracture had 2 fracture surface patterns. Spring B has a brittle fracture where the shape of the fracture is more even and does not show residual fracture. While springs A, C, and D experienced ductile fracture. The results of metallography found corrosion products in the surface area of the spring. There are non-metallic inclusions in the form of sulfides and microvoids. The microstructure is tempered martensite. From the results of the chemical composition of the spring material, it still meets the JIS G 4801 grade SUP 12 standard with the addition of Silicon and Chrome. The hardness test results have a hardness value of 518.4 HV. The spring hardness value is above the maximum hardness limit of SUP 12 material. The SEM test results of the spring sample show the presence of non-metallic inclusions with elongated morphology and micro-sized voids. The results of the EDX test showed a Sulfur content of 4.71 wt% in non-metallic inclusions and the content of Fe and O elements in the defective holes which were corrosion products. From this study, it is known that the factors causing damage to the springs are manufacturing process errors, material defects, and corrosive environments.